THE IMPACT OF INTERNET SIGNALS ON THE NUMBER OF INDEPENDENT VILLAGES - Ari Saputro (Integrative Perspectives of Social and Science Journal, 2026)
This study analyzes the impact of internet signal availability on the number of independent villages in Indonesia in 2021, using data from the Central Bureau of Statistics of Indonesia. This research employs a descriptive method. The analyzed data includes the number of independent villages per province from 2019 to 2021 and the availability of internet signals (4G/LTE, 3G/H/H+, 2.5G/E/GPRS, and no signal) in villages/sub-districts. The results of the analysis show a very strong positive correlation between the availability of 4G/LTE signals and the number of independent villages. Villages with access to 4G/LTE signals are more likely to achieve independent status compared to those with access to lower signals or no signals at all. A strong correlation was also found with 3G/H/H+ and 2.5G/E/GPRS signals, although slightly lower compared to 4G/LTE signals. This conclusion underscores the importance of access to digital infrastructure in supporting village independence. However, this analysis is limited to correlational relationships, so further research is needed to explore other factors contributing to village independence. These findings provide insights for policymakers and stakeholders in developing more effective village development strategies by leveraging information and communication technology.